Linking Corporate Social Responsibility To Financial Performance: Evidence From Small And Medium-sized Enterprises - Mansing, Fritzie Megan P.; Palo, Maureen Kaye C.; Sarabia, Nissy A.; Sumicad, Eligen H. (Faculty Of Islamic Economics and Business, 2025)
Purpose: This study investigates the impact of Corporate Social Responsibility (CSR) practices on the financial performance of Small and Medium-Sized Enterprises (SMEs) in Pagadian City, Philippines.Design/methodology/approach: The study employs a descriptive-correlational methodology to evaluate how CSR practices in key areas—community, environment, employees, customers, and suppliers—affect business financial outcomes. A survey involving 78 SMEs was conducted using adapted structured questionnaires. The results were then analyzed using descriptive statistics and the Pearson correlation method to determine the strength of the relationship.Research Findings: Findings indicate a strong positive and significant relationship between the implementation of Corporate Social Responsibility practices and the financial performance of SMEs. Businesses that actively engage in CSR, particularly in socially responsible initiatives, experience enhanced financial stability and increased profitability. These findings suggest that CSR can serve as a strategic tool for SMEs to not only fulfill ethical business conduct but also to improve competitiveness and promote long-term financial success.Contribution/Originality/Novelty: Results offer practical implications for SME owners, policymakers, and academic researchers, stressing the growing importance of integrating CSR into the core business strategies for sustainable growth, mainly focusing on the SME sector. Tujuan Penelitian: Penelitian ini menyelidiki dampak praktik Corporate Social Responsibility (CSR) terhadap kinerja keuangan Usaha Kecil dan Menengah (UKM) di Kota Pagadian, Filipina.Desain / metodologi / pendekatan: Penelitian ini menggunakan metodologi deskriptif-korelasional untuk mengevaluasi bagaimana praktik CSR di lima bidang utama—komunitas, lingkungan, karyawan, pelanggan, dan pemasok—mempengaruhi hasil keuangan bisnis. Data dikumpulkan melalui survei terhadap 78 UKM menggunakan kuesioner terstruktur yang telah diadaptasi. Analisis data dilakukan dengan statistik deskriptif dan metode korelasi Pearson untuk menentukan kekuatan hubungan antara variabel.Temuan Penelitian: Hasil penelitian menunjukkan adanya hubungan positif yang kuat dan signifikan antara penerapan praktik CSR dan kinerja keuangan UKM. Bisnis yang aktif dalam kegiatan CSR, khususnya inisiatif yang bertanggung jawab secara sosial, mengalami peningkatan stabilitas keuangan dan profitabilitas.Kontribusi / Orisinalitas / Kebaruan: Hasil penelitian ini memberikan wawasan bagi pemilik UKM, pembuat kebijakan, dan akademisi mengenai pentingnya integrasi CSR dalam strategi bisnis inti untuk meningkatkan daya saing dan pertumbuhan keuangan yang berkelanjutan di sektor UKM